Are gender norm violations always perceived negatively? The effects of marital name choice on perceived work and relationship commitments - Kristin Kelley; Lena Hipp (European Sociological Review, 2025)
Women who keep their surnames after marriage violate the prescriptive stereotype that they should be communal and deferent, while men who change their names violate the stereotype that they should be agentic and individualistic. Drawing on data from a pre-registered survey experiment conducted with a national probability sample in Germany (N = 1,899), we test hypotheses derived from the prescriptive stereotype framework and examine whether gender norm violations are evaluated symmetrically for women and men. Our analyses show that men who break marital name norms by changing their surname are perceived to be less committed to their jobs but more committed to their relationships than men who keep their names. Women who break marital name norms by keeping their surnames are perceived as less committed to their relationships, but—unlike men—they are not `rewarded' with higher perceived professional commitment. In fact, name-keeping women are seen as no more committed to their jobs than name-changing women or men. These findings illustrate the persistence of prevailing gender role expectations and suggest that women have less flexibility than men to break gender norms in the family context, while men have less flexibility than women to break gender norms in the workplace context.
Keywords: 300